Impact of Incentive Granting Arrangements on The Implementation of Investment Activities in Indonesia - Isye Junita Melo; Feibe Engeline Pijoh; Joupy Gustav Zumondak Mambu; Vicky Aristo Katiandago (Technium Social Sciences Journal, 2023)
This study specifically aims to find, describe and analyze arrangements for giving incentives to investors according to Law No. 25 of 2007 concerning Investment and the impact of the arrangement of providing incentives for foreign investors towards the acceleration of development in Indonesia. The specific target to be achieved in this study is the improvement of government policies in regulating incentives for investment activities. The method used in this study is a normative legal research method, namely as one of the studies that is commonly known in the field of law to study the substance of positive law textually (not only against norms, but also principles, even values ​​that contained in it). The government provides convenience to investors who invest their capital, namely the convenience of expanding their business and making new investments. The incentives provided include direct incentives and indirect incentives. The impact of setting up incentives for foreign investors to accelerate development in Indonesia will be seen from the increasing number of investments coming into Indonesia. The total value of investment coming into Indonesia from year to year shows significant changes. That means, the investment policy implemented is capable of accelerating the development of investment in Indonesia.